The Principal's Leadership Role in Efforts to Improve Teacher Work Discipline at SD Negeri Kalbir - Sofiatul Azkiyah; Mulyanto (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to determine the role, inhibiting and supporting factors as well as solutions to the principal's leadership role in an effort to improve teacher work discipline at SD Negeri Kalbir. The type of research used qualitative with descriptive form. Data collection using observation, interviews, and documentation. The research subjects were the principal, class teachers. The results showed: 1)The principal carries out his role as an educator by providing role models and improving teacher professionalism; as a manager who plans everything related to the school. 2)The inhibiting factors; the status of some teachers is still honorary and the infrastructure is not complete, the supporting factor is the good personality of the teacher. 3)The solution is to update the school regulations.